1994
DOI: 10.1093/carcin/15.11.2593
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of propoxur on male rat bladder urothelium

Abstract: Propoxur produces bladder tumors in rats, but not other species. The hyperplastic and tumorigenic effects do not occur if urinary pH is lowered by administering propoxur in a semi-synthetic diet or co-administering it with ammonium chloride (NH4Cl). We fed propoxur at 8000 p.p.m. in Altromin 1321 diet to male Wistar rats for 4 weeks, with or without NH4Cl as 10,000 p.p.m. of the diet. The urine of rats fed control diet with or without propoxur had a relatively high urinary pH (approximately 8); the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In an in vivo study, propoxur failed *Abbreviations: SCE, sister chromatid exchange; NP, N-nitroso propoxur; RTE, rat tracheal epithelial; MEM, minimum essential medium; FBS, fetal bovine serum; BrdU, 5Ј-bromodeoxyuridine; PBS, phosphate buffered saline; BSA, bovine serum albumin; GJIC, gap junctional intercellular communication; DMSO, dimethyl sulfoxide; TPA, 12-O-tetradecanoylphorbol-13 acetate; 6TG, 6- to induce a significant number of chromosome aberrations or micronuclei (12). Recently, propoxur was reported to induce bladder tumors in rats, but not in other species (13). Further investigations are needed to elucidate the genotoxicity of propoxur.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vivo study, propoxur failed *Abbreviations: SCE, sister chromatid exchange; NP, N-nitroso propoxur; RTE, rat tracheal epithelial; MEM, minimum essential medium; FBS, fetal bovine serum; BrdU, 5Ј-bromodeoxyuridine; PBS, phosphate buffered saline; BSA, bovine serum albumin; GJIC, gap junctional intercellular communication; DMSO, dimethyl sulfoxide; TPA, 12-O-tetradecanoylphorbol-13 acetate; 6TG, 6- to induce a significant number of chromosome aberrations or micronuclei (12). Recently, propoxur was reported to induce bladder tumors in rats, but not in other species (13). Further investigations are needed to elucidate the genotoxicity of propoxur.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy is believed to arise from urinary pH, which is slightly alkaline in rats consuming Altromin 1321 but acidic in rats fed a casein-based diet. Cohen et al (1994) have demonstrated that a reduction of 1 pH unit or more is enough to inhibit urothelial proliferation and tumour formation in rats treated with propoxur.…”
Section: Dosing Routementioning
confidence: 99%
“…Diet, food and water consumption and body weight gains per se can also have an important influence on many aspects of animal responses, including shifts in metabolic, hormonal and homeostatic mechanisms (Kennedy, 1969), disease processes (Berg & Simms, 1960;Paynter, 1984;Ross & Bras, 1965;Tannenbaum, 1940;Cohen et al, 1994) and maturation (Innami et al, 1973). (See also Subsection 1.2.2.)…”
Section: Body Weight Changes and Food And Water Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sus propiedades tóxicas incluyen la inhibición de la acetilcolinesterasa, convulsiones violentas y trastorno neuromuscular si se inhala (Shiryō 1994). También se reporta que es teratogénico, genotóxico, mutagénico y afecta a los embriones (Cohen et al 1994;Gera et al 2011). Debido a su gran toxicidad y aplicabilidad se reportan varios métodos de cuantificación de sus residuos, dentro de los que están la espectrofotometría UV-Vis (Tamrakar et al 2007), la cromatografía líquida de alto rendimiento (Tennakoon et al 2009;Otieno et al 2010;Bermúdez et al 2011), la cromatografía de gases (Petropoulou et al 2006), la fluorimetría (Pacioni y Veglia 2003), los sensores amperométricos (Sun et al 2012) y la cromatografía de gases acoplada a espectrometría de masas (Bravo et al 2005;Tennakoon et al 2009;Otieno et al 2010).…”
Section: Introductionunclassified